Análisis jurídico, doctrinario y comparado del pago de pensiones vitalicias a ex mandatarios en el margen del régimen jurídico de la LOSEP - Inlago Pijal, Nadya Mishell (2024)
The present research work entitled “Legal, doctrinal and comparative analysis of the payment of life pensions to former officials in the margin of the legal regime of The Organic Law of Public Service”, the purpose of this study is to analyze the violation of the right to legal certainty regarding the payment of lifetime pensions to former presidents and vice presidents of the Republic of Ecuador who do not meet the requirements to be beneficiaries and those who, contrary to the law, have transferred this right to their relatives, despite the fact that the LOSEP in Article 136 states that only their heirs will be beneficiaries in case of death of the right holder, even the same law states that pensions are non-transferable. On the other hand, to identify inconsistencies, contradictions and legal loopholes. As well as carrying out a study of comparative law with legislation of Argentina, Colombia, Peru and Chile, in order to contrast, update the norm to the new needs or situations that arise such as the regulation and prohibition of double life pension, suspension of the pension when the person has an income that comes from state resources, as well as the need to establish a margin of temporality when this right is inherited to the spouse or children. All this with the purpose of adequately using the resources of the State.